2011
DOI: 10.4103/0972-124x.84387
|View full text |Cite
|
Sign up to set email alerts
|

Split mouth de-epithelization techniques for gingival depigmentation: A case series and review of literature

Abstract: Gingival melanin pigmentation occurs in all races of mankind. Although clinical melanin pigmentation does neither present itself as a medical problem nor a disease entity, it is a major esthetic concern for many people, especially Asians. Esthetic gingival depigmentation procedures can be performed in such patients with excellent results. This case series presents a split mouth de-epithelization procedure using popular surgical techniques such as scalpel, bur abrasion or electrosurgery. These techniques were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 37 publications
0
39
1
16
Order By: Relevance
“…Also, it has been reported that electrosurgery requires more expertise than scalpel surgery. 11 Here again, the results were in contrast to the present study, where dissection of the partial thickness flap by scalpel required more surgical expertize as compared to electrosurgery. 12 Electrosurgery, however, has the disadvantage that prolonged or repeated application of current to tissue induces heat accumulation and undesired tissue destruction.…”
Section: Discussioncontrasting
confidence: 98%
“…Also, it has been reported that electrosurgery requires more expertise than scalpel surgery. 11 Here again, the results were in contrast to the present study, where dissection of the partial thickness flap by scalpel required more surgical expertize as compared to electrosurgery. 12 Electrosurgery, however, has the disadvantage that prolonged or repeated application of current to tissue induces heat accumulation and undesired tissue destruction.…”
Section: Discussioncontrasting
confidence: 98%
“…24 Due to unaesthetic appearance, patients often demand depigmentation treatments. Pigmented layers may be removed by scalpel surgery, bur abrasion, 18 cryosurgery, 25 electrosurgery, laser therapy [26][27][28] and chemical agents such as 90% phenol and 95% alcohol. Pigmented gingiva can also be covered by a free gingival graft 29 or acellular dermal matrix allografts.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that electrosurgery required a lot of precision but increased the efficacy of work, giving a cleaner and neater work field. Scalpel de-epithelialization was reported to be easier and gave profound results and patient satisfaction 13 . However, no study compared these four methods in one patient as done in the present case report.…”
Section: Discussion:-mentioning
confidence: 99%
“…These include instant sterilization of surgical site, reduced bacteremia, less mechanical trauma, minimal post-operative scarring, swelling and post-operative pain. In a case series by Pradeep et al, split mouth de-epithelialization procedure using a scalpel, bur abrasion and electrosurgery were successfully used to treat gingival hyperpigmentation 13 . It was reported that electrosurgery required a lot of precision but increased the efficacy of work, giving a cleaner and neater work field.…”
Section: Discussion:-mentioning
confidence: 99%